Repositioning Islam as an Epistemic Paradigm in Postcolonial Critique: From Orientalism to the Decolonization of Knowledge - Abdul Somad (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Postcolonial scholarship has played an important role in exposing the enduring influence of colonial power on contemporary knowledge production. Nevertheless, Islam continues to be discussed predominantly as an object of representation instead of being recognized as an epistemic tradition capable of generating alternative theoretical perspectives. Responding to this gap, the present study explores how Islam can be repositioned as an epistemic paradigm within postcolonial discourse to support the broader project of decolonizing knowledge. This research adopted a qualitative conceptual approach based on systematic library research. Relevant literature was examined through thematic coding, Critical Discourse Analysis, and interpretative synthesis to identify recurring patterns and conceptual relationships. The analysis reveals that current postcolonial debates remain largely centered on dismantling Orientalist narratives while offering limited engagement with Islamic epistemological resources. In contrast, principles such as tawḥīd, al-'adl, maṣlaḥah, and amānah provide a coherent ethical and philosophical foundation for advancing epistemic pluralism and challenging contemporary forms of coloniality. Building on these findings, the study proposes an Islamic postcolonial epistemic framework that reconnects Islamic intellectual traditions with postcolonial criticism, thereby expanding ongoing discussions on epistemic justice and promoting a more inclusive understanding of global knowledge production.